2016
DOI: 10.1111/jfq.12231
|View full text |Cite
|
Sign up to set email alerts
|

Oxidative and Microbial Stability of Pomegranate Peel Extracts and Bagasse Supplemented Cookies

Abstract: This study aimed at exploring pomegranate peel (PoP) for its potential as an ingredient of choice in baked products primarily to stabilize lipids and inhibit microbiological spoilage. Pomegranate peel extracts (PoPx) and pomegranate peel bagasse (Pbg) were supplemented to wheat flour cookies at 0.25–1.0% and 1.5–7.5%, respectively. Cookies supplemented with 7.5% Pbg reduced caloric contents and significantly (P < 0.05) enhanced dietary fiber and inorganic residues of the product. Positive correlation was obser… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
14
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(15 citation statements)
references
References 47 publications
1
14
0
Order By: Relevance
“…8 These increments were kept throughout storage ( p > 0.05). Ismail et al (2016) also reported an increase of 1.64-fold on TPC when PPE was incorporated in wheat flour cookies at a concentration of 2.5 mg PPE per g flour. 13 Similar results were found when PPE was added to dealcoholized wine, 42 icecream, 54 curd, 55 and carabeef nuggets.…”
Section: Food and Function Papermentioning
confidence: 87%
See 2 more Smart Citations
“…8 These increments were kept throughout storage ( p > 0.05). Ismail et al (2016) also reported an increase of 1.64-fold on TPC when PPE was incorporated in wheat flour cookies at a concentration of 2.5 mg PPE per g flour. 13 Similar results were found when PPE was added to dealcoholized wine, 42 icecream, 54 curd, 55 and carabeef nuggets.…”
Section: Food and Function Papermentioning
confidence: 87%
“…Ismail et al (2016) also reported an increase of 1.64-fold on TPC when PPE was incorporated in wheat flour cookies at a concentration of 2.5 mg PPE per g flour. 13 Similar results were found when PPE was added to dealcoholized wine, 42 icecream, 54 curd, 55 and carabeef nuggets. 56 The similarity of TPC between both treatments can be explained by the presence of other subfamilies of phenolic compounds, such as phenolic acidsknown to be present in pomegranate peel.…”
Section: Food and Function Papermentioning
confidence: 87%
See 1 more Smart Citation
“…Pomegranates are commonly consumed in the form of juices, jams, jelly squash, syrup, and nectar. Pomegranate peels are the main byproduct obtained through juice processing, together with pulp and bagasses [53]. Recent studies on the functional and nutraceutical properties of pomegranate peel suggest a significant presence of ellagitannins, flavonoids and anthocyanins, which have important health significance [53].…”
Section: Pomegranate Byproductsmentioning
confidence: 99%
“…Pomegranate peels are the main byproduct obtained through juice processing, together with pulp and bagasses [53]. Recent studies on the functional and nutraceutical properties of pomegranate peel suggest a significant presence of ellagitannins, flavonoids and anthocyanins, which have important health significance [53]. Ellagitannins, the main hydrolysable tannins of pomegranate, possess antimicrobial, antioxidant, anti-mutagenic, anticancer, anti-inflammatory, anti-diabetic, and other properties beneficial to health [16].…”
Section: Pomegranate Byproductsmentioning
confidence: 99%